2021
DOI: 10.3389/fgwh.2021.651752
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive to Infection but Strong in Defense—Female Sex and the Power of Oestradiol in the COVID-19 Pandemic

Abstract: The incidence of SARS-CoV2 infections is around 15% higher in premenopausal women compared to age matched men, yet the fatality rate from COVID-19 is significantly higher in men than women for all age strata. Sex differences have also been observed in recent epidemics including severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS), with SARS-CoV 2 virus infection sex differences appear more dramatic. The regulation and expression of the angiotensin converting enzyme 2 (ACE2) is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…In addition, the healthcare workforce is more likely to be visited by physicians 8,30 . Another justification is that females are sensitive to health situations and skin problems 38 . However, there is no definite identified reason for this issue and requires to be addressed in forthcoming studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the healthcare workforce is more likely to be visited by physicians 8,30 . Another justification is that females are sensitive to health situations and skin problems 38 . However, there is no definite identified reason for this issue and requires to be addressed in forthcoming studies.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the type of contraceptive, hormonal contraceptive use alters hormonal cyclicity, which can influence both menstrual cycle features and immune cyclicity, and therefore could potentially affect COVID-19 symptom severity. Some authors have claimed that estradiol, a component of the combined hormonal contraceptive pill, offers a protective effect against COVID-19 severity and mortality, 56 and a study using data from the COVID Symptom Tracker App reported that women aged 18–45 taking the combined oral contraceptive pill had lower rates of predicted COVID-19 and lower hospital attendance than women taking no form of hormone therapy 57 (although the role of residual confounding, most notably by age, cannot be ruled out). Hormonal contraceptive use might also be an effect modifier, for example pandemic-related exposures might affect features of contraceptive-controlled menstrual cycles differently from those of natural cycles.…”
Section: Potential Research Biasmentioning
confidence: 99%
“…An earlier survey has also emphasized that the incidence of SARS-CoV-2 infection is approximately 15% higher in premenopausal women than men in some age ranges. However, COVID-19 mortality among men is significantly higher than in women of all ages ( 26 ), but this outcome was reverse in some other studies ( 27. , 28.…”
Section: Discussionmentioning
confidence: 87%